An International Normalized Ratio–Based Definition of Acute Traumatic Coagulopathy Is Associated With Mortality, Venous Thromboembolism, and Multiple Organ Failure After Injury. Issue 7 (July 2015) - Peltan, Ithan D.; Vande Vusse, Lisa K.; Maier, Ronald V.; Watkins, Timothy R.
Abstract : Objectives: Acute traumatic coagulopathy is associated with adverse outcomes including death. Previous studies examining acute traumatic coagulopathy's relation with mortality are limited by inconsistent criteria for syndrome diagnosis, inadequate control of confounding, and single-center designs. In this study, we validated the admission international normalized ratio as an independent risk factor for death and other adverse outcomes after trauma and compared two common international normalized ratio–based definitions for acute traumatic coagulopathy. Design: Multicenter prospective observational study. Setting: Nine level I trauma centers in the United States. Patients: A total of 1, 031 blunt trauma patients with hemorrhagic shock. Interventions: None. Measurements and Main Results: International normalized ratio exhibited a positive adjusted association with all-cause in-hospital mortality, hemorrhagic shock-associated in-hospital mortality, venous thromboembolism, and multiple organ failure. Acute traumatic coagulopathy affected 50% of subjects if defined as an international normalized ratio greater than 1.2 and 21% of subjects if defined by international normalized ratio greater than 1.5. After adjustment for potential confounders, acute traumatic coagulopathy defined as an international normalized ratio greater than 1.5 was significantly associated with all-cause death (odds ratio [OR], 1.88; p < 0.001), hemorrhagic shock–associated death (OR, 2.44; p = 0.001), venous thromboembolism (OR, 1.73; p < 0.001), and multiple organ failure (OR, 1.38; p = 0.02). Acute traumatic coagulopathy defined as an international normalized ratio greater than 1.2 was not associated with an increased risk for the studied outcomes. Conclusions: Elevated international normalized ratio on hospital admission is a risk factor for mortality and morbidity after severe trauma. Our results confirm this association in a prospectively assembled multicenter cohort of severely injured patients. Defining acute traumatic coagulopathy by using an international normalized ratio greater than 1.5 but not an international normalized ratio greater than 1.2 identified a clinically meaningful subset of trauma patients who, adjusting for confounding factors, experienced more adverse outcomes. Targeting future therapies for acute traumatic coagulopathy to patients with an international normalized ratio greater than 1.5 may yield greater returns than using a lower international normalized ratio threshold. Abstract : Supplemental Digital Content is available in the text.